British Army in America collection
Letters and documents relating primarily to the British Army's defense of Penobscot Bay, Halifax, and Canada during the American Revolution. Includes letters concerning the French and Indian War. Correspondents include Sir Henry Clinton; Guy Carleton, Baron Dorchester; Sir Frederick Haldimand; William Petty, Marquis of Lansdowne; and Francis MacLean.
Index available in the Library of Congress Manuscript Reading Room.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Clinton, Henry, -- Sir, -- 1738?-1795 -- Correspondence; Dorchester, Guy Carleton, -- Baron, -- 1724-1808 -- Correspondence; Haldimand, Frederick, -- Sir, -- 1718-1791 -- Correspondence; Lansdowne, William Petty, -- Marquis of, -- 1737-1805 -- Correspondence; MacLean, Francis, -- 1717?-1781 -- Correspondence; Great Britain. -- Army; Canadian Invasion, 1775-1776.; Penobscot Expedition, 1779.; Canada -- History -- 1755-1763.; Halifax (N.S.) -- History; Maine -- History -- Revolution, 1775-1783.; Nova Scotia -- History -- 1775-1783.; United States -- History -- French and Indian War, 1755-1763.; United States -- History -- Revolution, 1775-1783 -- British forces